PERBANDINGAN PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE STUDENT TEAMS ACHIEVEMENT DIVISION (STAD) DAN TEAMS GAMES TOURNAMENTS (TGT) TERHADAP HASIL BELAJAR LOMPAT JAUH GAYA JONGKOK - BAGUS LESMANA, INDRA (Jurnal Pendidikan Olahraga dan Kesehatan, 2014)
Abstract In long jump, jumper will try to move forward with footing on beam hardly for landing in long jump sand box far away. In long jump lesson there are many styles and one of them is long jump squat style which has special character when flying in the air body position like a people’s squating. The questions in this research are, is there any different of implementation cooperative learning model between STAD and TGT type, how big much the different and which one the bigger influence toward long jump squat style learning product on students of 7th graders SMP Negeri 1 Mojosari, Mojokerto. STAD is one of learning model with group system, one of students will choose by the teacher as an expert student who will explain to his group. TGT is one of cooperative learning model where learning activity uses game growing responsility, teamwork, and fairplay. With implementation of STAD and TGT will known the bigger influence toward long jump squat type learning product. This research is experiment research that uses descriptive quantitative. Sample in this research is 63 students, which consist from 32 students of VIIC as an experiment group X1 STAD and 31 students of VIID as an experiment group X2 TGT. Form accounting T-Test Independent, it can conclude that there is no different between STAD and TGT type toward long jump squat style learning product which is proved from Tcount=0,22 less than Ttable (0,22<2,99). Cooperative learning model which is the bigger influence toward long jump squat style learning product on students of  7th graders SMP Negeri 1 Mojosari, Mojokerto is TGT with increases as big as 52,02%. Keyword: Cooperative learning STAD and TGT type, Long jump squat style, Learning product